Dynamic change of PD-L1 expression on circulating tumor cells in advanced solid tumor patients undergoing PD-1 blockade therapy. (3rd July 2018) - Yue, Chunyan; Jiang, Yubo; Li, Ping; Wang, Yuehua; Xue, Jian; Li, Nannan; Li, Da; Wang, Ruina; Dang, Yongjun; Hu, Zhiyuan; Yang, Yanlian; Xu, Jianming
ABSTRACT: Background: Tumor PD-L1 levels have predictive value in PD-1/PD-L1 checkpoint blockade therapies, yet biopsies can only provide baseline information. Whether PD-L1 expression on circulating tumor cells (CTCs) could serve as an alternative biomarker is of great interest. Design: We established an immunofluorescence assay for semi-quantitative assessment of the PD-L1 expression levels on CTCs with four categories (PD-L1 negative, PD-L1 low, PD-L1 medium and PD-L1 high ). 35 patients with different advanced gastrointestinal tumors were enrolled in a phase 1 trial of a PD-1 inhibitor, IBI308. The CTC numeration and the PD-L1 expression levels were analyzed. Results: Prior the treatment of IBI308, 97% (34/35) patients had CTCs, ranging from1 to 70 (median 7). 74% (26/35) had PD-L1 positive CTCs, and 60% (21/35) had at least one PD-L1 high CTCs. The disease control (DC) rate in PD-L1 high patients (48%) is much higher than the others (14%). The group with at least 20% abundance of PD-L1 high CTCs had even higher DC rate of 64% (9/14), with only 14% DC rate for the rest (3/21). We also observed that the count changes of total CTC, PD-L1 postive CTC and PD-L1 high CTC correlate quite well with disease outcome (P<0.001, P = 0.002 and 0.007, respectively). In addition, the abundance of PD-L1 high CTCs at baseline had predicative significance for progression free survival (PFS). Conclusions: We revealed that the abundance of PD-L1 high CTCs at baseline might serve as a predictor to screen patients for PD-1/PD-L1 blockade therapies and measuring the dynamic changes of CTC could indicate the therapeutic response at early time.